Serum Albumin Concentration and the Risk of Cardiovascular Disease and Acute Coronary Syndrome — a Narrative Review - Czinege Maria; Ruța Florina; Nyulas Victoria; Halațiu Vasile-Bogdan; Nyulas Tiberiu; Benedek Theodora (Journal of Cardiovascular Emergencies)
Cardiovascular diseases are the primary cause of global health decline. Conditions that cause inflammation and excessive oxidation are present in the early development of the majority of cardiovascular diseases, including coronary artery disease and heart failure. Among the many physiological functions of albumin, its antioxidant, anti-inflammatory, anticoagulant, and antiaggregant properties are the most important. Low serum albumin levels are associated with the occurrence of various cardiovascular diseases such as coronary artery disease, stroke, heart failure, and atrial fibrillation. Several recent meta-analyses support the idea that hypoalbuminemia may act as a modifiable risk factor that increases oxidative stress and inflammation, contributing to the development and progression of cardiovascular diseases. However, it is unclear whether correcting hypoalbuminemia can improve outcomes for patients with cardiovascular diseases and reduce mortality rates. In this regard, further research is crucial.